1981
DOI: 10.1128/jvi.39.2.390-400.1981
|View full text |Cite
|
Sign up to set email alerts
|

XbaI, PstI, and BglII restriction enzyme maps of the two orientations of the varicella-zoster virus genome

Abstract: Cleavage of varicella-zoster virus DNA with the restriction endonucleases PstI, XbaI, and BglII resulted in 18, 22, and 20 fragments, respectively. Based on the molecular weights and molarities of these fragments, a molecular weight of 84 x 106 could be calculated for the varicella-zoster virus genome. In both the XbaI and the BglII patterns, four 0.5 M fragments were identified. The arrangement of the fragments was determined by molecular hybridization techniques, and the terminal fragments were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Recombination in tissue culture has been used in the analysis of herpes simplex virus (HSV) mutants [reviewed by Schaffer, 19811, and in the study of genome segment inversion [Ben-Porat, et al, 1984;Chou and Roizman, 1985;Davison and Wilkie, 1983a,bJ. Recombination has also been noted during experimental infection of animals with HSV strains [Gerdes and Smith, 1983;Javier, et al, 19861. Recombination most likely also occurs during varicella-zoster virus (VZV) infection because the genome has a short segment (Us) flanked by inverted repeats (IRs, TR,) which is inverted relative to the rest of the genome in 50% of the molecules [Davison and Scott, 1983;Dumas et al, 1981;Ecker and Hyman, 1982;Gilden et al, 1983;Mishra et al, 1984;Straw et al, 19821. Sheldrick and Berthelot [ 19741 first suggested that such inversions occurred by recombination in the flanking inverted repeat sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination in tissue culture has been used in the analysis of herpes simplex virus (HSV) mutants [reviewed by Schaffer, 19811, and in the study of genome segment inversion [Ben-Porat, et al, 1984;Chou and Roizman, 1985;Davison and Wilkie, 1983a,bJ. Recombination has also been noted during experimental infection of animals with HSV strains [Gerdes and Smith, 1983;Javier, et al, 19861. Recombination most likely also occurs during varicella-zoster virus (VZV) infection because the genome has a short segment (Us) flanked by inverted repeats (IRs, TR,) which is inverted relative to the rest of the genome in 50% of the molecules [Davison and Scott, 1983;Dumas et al, 1981;Ecker and Hyman, 1982;Gilden et al, 1983;Mishra et al, 1984;Straw et al, 19821. Sheldrick and Berthelot [ 19741 first suggested that such inversions occurred by recombination in the flanking inverted repeat sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the basic structure of VZV DNA. There are two unique sequences, UL, and Us, and one set of inverted repeats, TRs and IRS (6,7,16). Recently, it has been suggested that both the UL and Us sequences may be capable of inversion, the former at low frequency (14a; A. Davison, personal communication).…”
mentioning
confidence: 99%
“…Hybridization of pORF2-VZVgC1 DNA to restriction endonuclease fragments of VZV genomic DNA should specify uniquely the map location of the gC glycoprotein gene. Purified VZV viral DNA was digested with each of six restriction endonucleases whose sites had been mapped previously on the viral genome (7)(8)(9)25). Figure 4 demonstrates a Southern blot analysis of these restriction digests after hybridization to a pORF2-VZVgC1 DNA probe.…”
Section: Resultsmentioning
confidence: 99%